(untitled) - Maithel, Shishir Kumar (New York, 2006)
This concise, pocket sized guide to Critical Care medicine provides at-a-glance information for treating patients effectively and expiediently. Includes a free PDA download to facilitate its usefulness at the point of care.
Keywords: Critical care medicine,Critical Care,Critical Illness,Intensive Care Units,Chăm sóc y tế; Methods,Những phương pháp